PENGUATAN MANAJEMEN PENGELOLAAN KELOMPOK PEKARANGAN PANGAN LESTARI (P2L) AGROWISATA ADILUHUR (SALUR) MENUJU DESA WISATA INTERNASIONAL BERBASIS KETAHANAN PANGAN - Arief Rais Bahtiar; Yulian Zetta Maulana; Muhamad Yayandi (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The Community Service Program (PKM) in Adiluhur Tourism Village was implemented to address challenges faced by the SALUR Sustainable Food Garden (P2L), which previously lacked structured management, documentation, and integration with the village’s tourism sector. Initial observations revealed the absence of standard operating procedures, weak production records, and limited digital identity, resulting in minimal added value for both food security and tourism. This program aimed to strengthen P2L’s management capacity, integrate it into educational agro-tourism, and establish digital branding through official platforms. The implementation method was comprehensive, consisting of situational analysis, technology development, capacity-building training, intensive mentoring, and evaluation. Key innovations included the introduction of the Telang Dry infrared-based flower dryer, which improved product quality and efficiency, and the creation of an interactive marketplace website to support digital marketing and storytelling of local products. Training activities covered SOP-based management, production documentation, organizational structuring, digital marketing, and tourism integration, delivered through participatory workshops involving community members, youth, and local tourism actors. The program outcomes demonstrated significant improvements: P2L management is now documented with SOPs and organizational structures, agro-tourism packages have been developed, and digital branding has been established through an official website and active social media. These transformations distinguish the post-program condition from the previous state, contributing to enhanced food security, local economic growth, and the visibility of Adiluhur Tourism Village as a sustainable educational destination. The success of this initiative highlights the effectiveness of the training–mentoring–technology approach and its relevance to achieving SDGs and higher education performance indicators.